IMPROVING STUDENTS’ SPEAKING SKILL USING COMMUNICATIVE LANGUATE TEACHING - Juni Bayu Saputra; Hesti Tusiana Dewi (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2015)
This article points out the results of the study attempting to solve thespeaking problem faced by students in one of the Secondary School inEast Lampung. For the purpose of the topic, 35 students were selectedas the subject. Research method was Classroom Action Research withKemmis and Taggart model. It was conducted for about four cycles.According to the results of speaking test, findings showed that usingCommunicative Language Teaching (CLT) had positive meaningfuleffect on improving students’ speaking skill. To sum up, CLT is aneffective method to teach speaking to the subject.